Electronic doping-enabled transition from n- to p-type conductivity over Au@CdS core–shell nanocrystals toward unassisted photoelectrochemical water splitting. Issue 40 (1st October 2019) - Pan, Rongrong; Liu, Jia; Li, Yuemei; Li, Xinyuan; Zhang, Erhuan; Di, Qiumei; Su, Mengyao; Zhang, Jiatao
Abstract : Here we show a novel strategy for tailoring the synergistic electrical properties of metal@semiconductor hybrid nanocrystals (HNCs) based on cation exchange-enabled electronic doping. Abstract : Here we show a novel strategy for tailoring the synergistic electrical properties of metal@semiconductor hybrid nanocrystals (HNCs) based on cation exchange-enabled electronic doping. As a demonstration, the conductive nature of Au@CdS core–shell HNCs was changed from n- to p-type by introducing Cu dopants into the CdS shell. The dependence of the conductivity type on the dopant concentration in the HNCs is disclosed by combined photoelectrochemical (PEC) studies. Moreover, a tandem PEC cell consisting of an undoped Au@CdS photoanode and a Cu-doped Au@CdS photocathode respectively modified with cocatalysts is fabricated, which displayed stable H2 and O2 evolution in unassisted PEC overall water splitting.